Pengaruh Penambahan Aditif Sikament-Ln terhadap Kuat Tekan Beton Mutu Tinggi dengan Variasi Nilai Slump - Ibrahim Ibrahim; Kosim Kosim; Firdha Razhanah; Reynaldy Aji Nugraha; R. Reza Fahruddin (Jurnal Talenta Sipil, 2023)
High-strength concrete listed in SNI 03-6468-2000 concrete is defined as concrete having the required compressive strength of fc'≥ 41 Mpa. From this study, data obtained from the compressive strength of concrete at the age of 28 days as follows: the value of the normal concrete compressive strength of 41.72 MPa, the compressive strength of the Sikament-ln mixture of 0.6% slump 5 of 45.65 MPa, the compressive strength of the Sikament-mixed concrete. -ln 1% slump 6 of 47,38 MPa, compressive strength of mixed concrete Sikament-ln 1.4% slump 7 of 44.20 MPa, compressive strength of mixed concrete of Sikament-ln 1.8% slump 8 of 45.65 MPa 38 ,65MPa. It can be seen from the results of this study that the ideal compressive strength is the compressive strength of the Sikament-ln mixture of 1% slump 6 this is because the compressive strength value is much greater than the compressive strength without the Sikament-ln mixture.